Mozambique Crisis Response Plan 2020 - IOM - International Organisation for Migration (IOM - International Organisation for Migration, 2020)
The overall objective of IOM's strategy is to support displaced persons and other affected populations in Mozambique to build resilience and progress towards sustainable solutions to displacement while ensuring a continuous response to critical humanitarian needs and rapid response capacities in case of a new disaster and crisis. Recovery and resilience in Mozambique will be facilitated through an effective and locally owned framework that addresses the lifesaving and longer-term needs of affected populations. Ultimately, the plan aims at establishing the basis for recovery and crisis prevention in communities and continuing being a key partner of the Government of Mozambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; displaced communities / comunidades deslocadas